NOUNS OF RELIGION SEMANTIC ON -NITSA IN THE RUSSIAN LANGUAGE OF THE XVIII CENTURY (BASED ON LEXICOGRAPHIC WORKS OF CIVIL MEDIA) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-4-88-103The study deals with the problems of the history of the formation of the religious style of the Russian language. The article carried out a comprehensive linguistic analysis of the substances of religious semantics into -nitsa, registered in civil media dictionaries of the XVIII century. It was established that the nouns of religious semantics into -nitsa form a special layer of specific vocabulary with personal and non-personal meanings in the dictionary system of the religious style of the Russian language of the XVIII century. It is shown that the substances of religious semantics on the -nitsa are characterized by a system of complex word-forming relations and for the most part are monosemantic specific names that identify female persons by position, performed by professional functions or by action.Key words: religious style, Russian lexicography, noun names of religious semantics, suffix nits-, suffix -itz-, Orthodoxy, XVIII century